An experimental study of carboxylic acid prepared by carbon dioxide (CO2) - Khairil Izuan, Ahmad Tarmidzi (2010)
Carboxylic acid has been known as industrial chemical for many years and large amount are used in the manufacture of various product.There are several method has been used such as oxidation of primary alcohol,hydrolysis of acid derivative and carboxylation of Grignard reagent.The current situation of production of carboxylic acid using carbon dioxide as a source required a complex process which may cost higher investment.Yet,there still a lot of carbon dioxide that not fully recover and been release to the atmosphere which may influence the global warming issues. The production of carboxylic acid prepared by carbon dioxide (CO 2) has been studied using photosynthesis catalysis method.The main objective is to study the influenced of photosynthesis light and catalyst in carboxylic acid production.The study conducted using existing reactor and modified with addition of photosynthesis lamp.The carbon dioxide was injected into the reactor and reacts with calcium carbonate catalyst and let the reaction for 2 or 3 hours with difference flow rate of carbon dioxide.As the results,the acidity of the solution increased proportionally to the flow rate of carbon dioxide.The solution that been produced contains carboxylic acid and be proved through the Fourier Transform Infrared (FTIR). It‟s showed that the photosynthesis catalysis method applicable to the production of carboxylic acid and the flow rate of carbon dioxide will increase the amount of carboxylic acid.